On the role of inlet flow instabilities on horizontal initially stratified liquid-liquid flow development - Morgan,RG; Ibarra,R; Zadrazil,I; Markides,CN (2014)
For a given pair of fluid phases, liquid-liquid flows aregenerally described in terms of regimes (e.g. stratified, wavy ordispersed), which are a function of the Reynolds numbers of theindividual phases, the geometry of the flow, as well as the inletconditions and the distance from the inlet. Typically, injectingthe heavier phase at the bottom of the channel and the lighterphase at the top is the common inlet configuration whenestablishing a liquid-liquid flow for study in a laboratoryenvironment. This configuration corresponds to that expectedin a naturally separated flow orientation, on the assumption thatat long lengths the density difference between the two phaseswill lead to this arrangement of the two phases. In this study, aseries of experiments were designed to investigate the influenceof injecting the heavier phase at the top of the pipe rather thanat the bottom. This modification introduces the possibility ofphase breakup near the inlet by an additional instabilitymechanism (due to the density difference between the twoliquids), which would not appear had the phases beenintroduced in the conventional inlet flow arrangement. Weperform detailed flow measurements and observe that this flowarrangement gives rise to altered flow structures downstream.Moreover, our results suggest that the effects of this instabilitynear the inlet may persist along the pipe and influence theobserved flow behaviour even at long lengths.